Constraining the Parameterized Neutron Star Equation of State with Astronomical Observations. (1st May 2022) - Singha, Jaikhomba; Mullai Vaneshwar, S.; Kumar, Ankit
Abstract: We utilize the phenomenologically parameterized piecewise polytropic equations of state to study various neutron star properties. We investigate the compliance of these equations of state with several astronomical observations. We also demonstrate that the theoretical estimates of the fractional moment of inertia cannot explain all the pulsar glitches observed. We model the crust as a solid spheroidal shell to calculate the fractional moment of inertia of fast-spinning neutron stars. We also show that the braking index obtained in a simple magnetic dipole radiation model with a varying moment of inertia deviates significantly from the observed data. Future developments in both theory and observations may allow us to use the fractional moment of inertia and braking index as observational constraints for neutron star equation of state.